2015
DOI: 10.1515/cclm-2014-0748
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic blood biomarker proadrenomedullin for outcome prediction in patients with chronic obstructive pulmonary disease (COPD): a qualitative clinical review

Abstract: Plasma proadrenomedullin (ProADM) is a blood biomarker that may aid in multidimensional risk assessment of patients with chronic obstructive pulmonary disease (COPD). Co-secreted 1:1 with adrenomedullin (ADM), ProADM is a less biologically active, more chemically stable surrogate for this pluripotent regulatory peptide, which due to biological and ex vivo physical characteristics is difficult to reliably directly quantify. Upregulated by hypoxia, inflammatory cytokines, bacterial products, and shear stress and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 85 publications
3
15
1
Order By: Relevance
“…Even though triage scores are developed to predict high initial treatment priority, daily decisions have to take into account harmful adverse events to further improve early risk stratification. As biomarker, ProADM was shown to provide relevant prognostic information in regard to the risk for adverse events within several prior studies focusing on selected patient subgroups with CAP [3234], chronic obstructive pulmonary disease (COPD) [15, 35], or cardiovascular diseases [36, 37]. Our study now expands these findings and shows the prognostic value of ProADM for the first time in an unselected patient population.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Even though triage scores are developed to predict high initial treatment priority, daily decisions have to take into account harmful adverse events to further improve early risk stratification. As biomarker, ProADM was shown to provide relevant prognostic information in regard to the risk for adverse events within several prior studies focusing on selected patient subgroups with CAP [3234], chronic obstructive pulmonary disease (COPD) [15, 35], or cardiovascular diseases [36, 37]. Our study now expands these findings and shows the prognostic value of ProADM for the first time in an unselected patient population.…”
Section: Discussionsupporting
confidence: 73%
“…The recent TRIAGE trial found a high prognostic ability of the inflammatory marker pro-adrenomedullin (ProADM) for the prediction of 30-day mortality, intensive care unit (ICU) admission, and high initial treatment priority [13, 14]. ProADM was also found to be of a high prognostic utility in several other studies in patients with respiratory tract infections and sepsis [1521]. Physiologically, ProADM reveals natriuretic and vasodilatatory effects, and is expressed in different tissues, where it acts both as an autocrine and paracrine mediator [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…Along the same line, in our study but not in that of Stolz et al,11 investigators were informed to exclude patients with suspected heart failure or pneumonia. This may be of importance to explain the lower short-term prognostic value in our study compared to that of Stolz et al,11 since MR-proADM has been associated with cardiovascular stress and infection 28…”
Section: Discussioncontrasting
confidence: 52%
“…It is upregulated in inflammatory and infectious conditions, and expressed in many clinical conditions including sepsis, respiratory infections and pneumonia, as well as also heart failure and myocardial infarction (37, 38). ProADM has been used as a prognostic marker, either alone or in risk stratification with other hormonal propeptides in patients with sepsis and severe pneumonia (39).…”
Section: Clinical Chemistrymentioning
confidence: 99%